Effects of Standardized Ileal Digestible Lysine Level on Growth Performance in 230 to 285 lb DNA Finishing Pigs - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to estimate the SID Lys requirement for growth and feed efficiency of 230- to 285-lb DNA finishing pigs. A total of 679 barrows and gilts (600 × 241, DNA; initial BW of 228.8 ± 2.9 lb) were used in two separate studies lasting 21- and 28-d, respectively. Pens of pigs were blocked by BW and randomly allotted to 1 of 6 dietary treatments with 8 to 10 pigs per pen in a randomized complete block design. A similar number of barrows and gilts were placed in each pen. Dietary treatments were corn-soybean meal-based and formulated to 0.43, 0.50, 0.57, 0.64, 0.71, and 0.79% SID Lys, with 12 replications for the 0.43, 0.50, 0.57, 0.71, and 0.79% SID Lys treatments, and 11 replications for the 0.64% SID Lys treatment. Increasing SID Lys increased (linear,P= 0.043) ADG, and improved (quadratic,P= 0.020) feed efficiency, resulting in pigs fed the diet containing 0.71% SID Lys having the greatest final BW and most optimum F/G. At high and low ingredient and pig prices, increasing SID Lys increased (quadratic,P= 0.004) IOFC. The broken-line linear model to maximize ADG predicted that there was no further improvement past 0.64% SID Lys. For F/G, the broken-line linear model predicted that there was no further improvement past 0.59% SID Lys. At high ingredient and pig prices, the quadratic polynomial model for IOFC predicted maximum economic return at 0.64% SID Lys. Additionally, at low ingredient and pig prices, the quadratic polynomial model for IOFC predicted maximum economic return at 0.62% SID Lys. In summary, the optimal SID Lys level for DNA finishing pigs from 230- to 285-lb depends upon the response criteria, with growth performance maximized between 0.59 to 0.64% SID Lys. Economic responses were maximized between 0.62% SID Lys and 0.64% SID Lys.
Keywords: Amino acid; growth; lysine requirement; finishing pig